AUTOMATED CONTROL OF THE PROCESS OF SORTING FRUIT AND VEGETABLE RAW MATERIALS WITH MONITORING ENERGY CONSUMPTION TO INCREASE THE ENERGY EFFICIENCY OF PRODUCTION - Цвіркун, Людмил; Омельченко, Олександр; Цвіркун, Сергій; Перекрест, Володимир; Галінтовський, Владислав (SWorldJournal, 2025)
The article proposes an automated control system for the sorting process of fruit and vegetable raw materials with fast algorithms for analyzing the shape of raw materials to isolate poor-quality samples from the general flow with monitoring energy consum